The role of immunoglobulin superfamily domains in interactions of immune cells - Barclay, Neil (Henry Stewart Talks, 2020)
Immunoglobulin superfamily (IgSF) domains, Leukocytes, Immunoglobulin structure, Leukocyte membrane proteins, Cell-surface protein interactions, Shape and size of membrane proteins, Rapid evolution of membrane proteins